Evaluation of Incidence, Genotypes, and Risk Factors Associated with Newly Diagnosed Hepatitis C Cases in Khyber Pakhtunkhwa (KPK), Pakistan - Najeeb Ullah Khan; Ubaid Ahmad; Maaz Iqbal; Muhammad Ismail; Adeela Mustafa (Current Trends in OMICS, 2022)
Hepatitis C is a global health concern brought on by the hepatitis C virus (HCV). The risk factors of the disease include injection drug users, contaminated medical instruments, blood transfusion, organ transplant, major surgery, dialysis, dental surgery, and acupuncture. The aim of the current study was to identify the prevalence of active HCV infection, genotypes, and their associated risk factors in newly infected patients of Khyber Pakhtunkhwa (KPK), Pakistan. A total of 230 HCV cases and 245 control subjects were enrolled. Our findings revealed that disease infection rates were higher in female patients (52.6%) than male patients (47.4%). Moreover, the disease was more prevalent in the age group 30–40 years (39.6%). The highest incidence was found in the southern region (51.30%), followed by the northern region (27.82%), and central region (18.26%). In our data set, dental surgery, major surgery, disease in family, barber community, blood received, needles, abroad travel, injection drug users, acupuncture, and organ transplantation were determined as the major associated risk factors of the disease. Odds ratio were significantly higher (10.91%) for those who used acupuncture as compared to those who did not. Similarly, odds were significantly higher (10.03%) for those who had HCV in their family, dialysis (9.377%), dental surgery (7.618%), major surgery (6.813%), barber community (5.328%), and blood received (2.252%) as compared to the control group. Also, the most frequent genotype was 3a (63%), followed by an un-typeable genotype (11.30%).